The ecology book - Juniper, Tony (New York, New York : DK Publishing, 2019)
"With concern about the environment at the top of the world agenda, there has never been a better time to get to grips with the theories that drive ecology. Since the earliest times, observers of the natural environment have sought to make sense of the world around them, by classifying nature to impose a sense of order and establish the relationships between different organisms, both living and extinct. But the scientific discipline of ecology--the study of how organisms interact with each other and their environment, and the structure and function of ecosystems--is relatively young. It encompasses the work of many disciplines, including biologists, chemists, climatologists, geographers, mathematicians, physicists, and zoologists, and builds on the views of influential figures both past and present, from Aristotle, Carl Linnaeus, [Alexander von Humboldt], and Charles Darwin, to Alfred Wegener, Rachel Carson, Jane Goodall, and James Lovelock. The Ecology Book examines more than 90 groundbreaking ideas that have shaped our understanding of the biodiversity on our planet--and the need to protect it. Nine themed chapters cover the story of ecology from ideas about evolution to environmental activism; they reveal how, even from the earliest times, we have been fascinated by our planet, striving to fathom its origins, explain its history, exploit its power, and even attempt to predict its future. The eye-catching visual approach includes memorable quotes, graphics, and feature boxes highlighting 'green' issues, such as the reforestation of the Amazon, the threats to coral reefs, and the pros and cons of genetic engineering. Authoritative an accessible, [this book] is he ideal introduction to arguably the most important subject of modern times."--Dust jacket.
The story of evolution -- Ecological processes -- Ordering the natural world -- The variety of life -- Ecosystems -- Organisms in a changing environment -- The living earth -- The human factor -- Environmentalism and conservation.
Includes index.
Keywords: Ecology -- Popular works